Transparent cosmetic and personal care compositions
By using cationic polymers in the transparent conditioner and ethoxylated anionic surfactant, the problem of low deposition efficiency of pirocone compounds in the prior art is solved, and efficient deposition and excellent anti-dandruff effect are achieved, while maintaining the transparent and low foaming properties of the composition.
Patent Information
- Application Number
- CN202380059524.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-15
- Filing Date
- 2023-08-01
- Publication Date
- 2025-04-08
AI Technical Summary
Existing transparent conditioners are difficult to effectively deposit pirocone compounds on the hair and scalp, and at the same time, there is a high detergent effect, resulting in low deposition efficiency of pirocone.
A transparent anti-dandruff conditioner composition was prepared by combining cationic polymers with ethoxylated anionic surfactant containing a large number of ethylene oxide groups, which significantly improved the deposition efficiency of the pirocone compound.
The efficient deposition of pirocronone compounds on hair and scalp is achieved, providing excellent anti-dandruff effect while reducing detergent effects, and the composition is transparent and low foaming.
Smart Images

Figure BDA0005270171510000051 
Figure BDA0005270171510000111 
Figure BDA0005270171510000121
Abstract
Description
Field of the Invention
[0001] The present invention relates to transparent antidandruff conditioner compositions and methods of treating hair using the same. Background of the Invention
[0003] Cosmetic and personal care compositions are often required to possess a variety of visual and functional attributes. For example, in order to be attractive to consumers, shampoo and hair conditioner compositions are often required to have properties beyond the ability to clean and / or condition the hair.
[0004] Clear, transparent compositions are often visually pleasing but difficult to formulate.Additional benefit agents, such as anti-dandruff agents, can cause undesirable effects such as clouding and discoloration.
[0005] Hair conditioners are usually used after shampooing and need to provide a high level of conditioning feel (smooth, smooth, lubricated, detangled) to wet hair. Consumers do not like foaming during use. Most conditioners are effective because they contain a dispersed lamellar gel phase that efficiently detangles. However, due to the presence of the dispersed phase, these are opaque. In the past, attempts were made to make the dispersed lamellar gel phase fragments small enough to make the composition transparent, but processing and stability problems occurred. Other known transparent conditioners are mainly based on polymers and are not very effective in providing conditioning benefits.
[0006] In contrast, shampoos are formulated to foam during use and therefore typically contain high levels of foaming cleansing surfactants, which are typically anionic, zwitterionic / amphoteric and nonionic in nature. Consumers associate foaming with cleaning performance. Shampoos provide a much lower level of conditioning benefits to hair, particularly when wet. Therefore, consumers use shampoo and conditioner simultaneously in a typical washing regime, traditionally first using shampoo and then using conditioner.
[0007] Anti-dandruff shampoos and conditioners may contain piroctone compounds, which are deposited on the hair and scalp during use. However, due to the detergency effect of the surfactants present in the formulation, the deposited piroctone active substance is not retained there. Therefore, piroctone is mostly washed off.
[0008] It is known to increase the amount of piroctone compounds to obtain increased anti-dandruff effects. For example:
[0009] WO2021 / 144267A1 discloses a personal cleansing composition, such as a shampoo, comprising i) a piroctone compound, ii) a cleansing surfactant comprising a given ratio of an amphoteric surfactant and an ethoxylated alkyl sulfate, and iii) a cationic polymer including polyquaternium-6, wherein the personal cleansing composition provides improved deposition of the piroctone compound on the scalp and / or hair surface during washing.
[0010] JP H1135424A provides specific guanidine derivatives in shampoos and anti-dandruff shampoos to obtain hair cosmetic and sensory conditioning benefits.
[0011] EP2944852A1 discloses the use of a synergist selected from alcohols having 2 to 5 hydroxyl groups and plant extracts to enhance the antidandruff or antiseptic activity of piroctone olamine in shampoos.
[0012] Despite the prior art, there remains a need for clear conditioner compositions which more effectively deposit piroctone compounds onto the hair and scalp during the washing process while having reduced soil removal.
[0013] We have now found that by using a cationic polymer in combination with an ethoxylated anionic surfactant containing a large amount of ethylene oxide groups, a transparent conditioner containing a piroctone anti-dandruff agent can be provided, thereby imparting excellent visual attributes without compromising conditioning performance and exhibiting minimal foaming. Surprisingly, such a transparent conditioner significantly improves the deposition efficiency of the piroctone compound, thereby providing excellent anti-dandruff benefits at lower piroctone levels. SUMMARY OF THE INVENTION
[0015] According to the present invention, in a first aspect, there is provided an aqueous conditioner composition comprising:
[0016] An aqueous conditioning agent composition comprising:
[0017] i) 0.1 to 2% by weight of a cationic conditioning polymer;
[0018] ii) 0.1 to 5% by weight of an ethoxylated anionic surfactant having a degree of ethoxylation of 3 to 15; and
[0019] iii) 0.001 to 2 wt%, preferably 0.01 to 1 wt%, more preferably 0.05 to 0.5 wt% of a piroctone compound;
[0020] The transparency of the composition is such that the turbidity is less than 1 cm -1, as measured using a UV / vis spectrophotometer and applying the formula turbidity = (2.3 x A / L), where A is the absorbance measured from the sample at 750 nanometers, and L is the path length;
[0021] wherein the composition has a maximum foam height of 10 ml as measured at 25°C and atmospheric pressure by diluting 1 gram of the composition with 9 grams of water in a 100 ml graduated cylinder having an inner diameter of 29 mm and recording the starting volume (V1); then stoppering the graduated cylinder and shaking it vertically vigorously for 10 seconds, followed by standing for 60 seconds, after which the height of the foam is measured to the nearest 5 ml mark; and subtracting the starting volume (V1) from this value; and
[0022] wherein the composition is free of anionic, zwitterionic and amphoteric surfactants other than those defined in ii) such that the foam height of the composition does not exceed the maximum foam height.
[0023] In a second aspect, the present invention provides a non-therapeutic method of treating the hair or scalp comprising applying to the hair or scalp a composition according to the first aspect of the invention. DETAILED DESCRIPTION OF THE INVENTION
[0025] The antidandruff composition of the present invention is transparent and low foaming.
[0026] The level of foaming produced by the compositions of the present invention may be measured using any suitable method. A preferred method is the Cylinder Shake Test as follows.
[0027] The drum shake test is preferably performed under ambient conditions (25°C and atmospheric pressure).
[0028] Dilute the test product (1 gram) with water (9 grams) and add to a 100 ml graduated cylinder. Record the starting volume (V1). Stopper the cylinder and shake it vigorously vertically for 10 seconds. After standing for an additional 60 seconds, visually measure the height of the foam to the nearest 5 ml mark. Subtract the starting volume of the solution (V1) from this value, and the result indicates the amount of air entrained in the foam, or the "foam height".
[0029] Suitable 100 ml glass cylinders are manufactured by Duran, supplied by VWR and have an internal diameter of 29 mm.
[0030] By this method, the maximum foam height produced by the composition of the present invention is 10 ml, preferably 7 ml, more preferably 5 ml.
[0031] A suitable method for assessing clarity is to measure turbidity. UV-vis spectroscopy can be used to determine the turbidity of a formulation. An example of a suitable spectrophotometer is the Jasco V-650 spectrophotometer.
[0032] Translucency (or turbidity) in liquid products is due to suspended or colloidal particles, which cause light to scatter rather than be transmitted in a straight line through the sample.
[0033] Turbidity can be calculated using the formula where turbidity is 2.3 times absorbance and divided by the path length of the sample, i.e., turbidity = (2.3 x A / L); where A is the absorbance of the sample measured at 750 nanometers and L is the path length. Preferably, a path length of 1.0 centimeters is used.
[0034] When the turbidity is less than 1 cm -1 , preferably less than 0.5 cm -1 , more preferably less than 0.4 cm -1 , even more preferably less than 0.25 cm -1 , most preferably less than 0.1 cm -1 When turbidimetric is 0.0447 W / m, the composition is considered transparent as measured using a UV / Vis spectrophotometer and applying the formula Turbidimetric = (2.3*A / L), where A is the absorbance measured from the sample at 750 nanometers and L is the path length.
[0035] Cationic Conditioning Polymers
[0036] The compositions of the present invention comprise at least one cationic conditioning polymer.
[0037] The cationic conditioning polymer is present in an amount of from 0.1 to 2 wt%, preferably from 0.1 to 1 wt%, based on the total weight of the composition.
[0038] Preferably, the polymer has a polysaccharide backbone, wherein the polysaccharide comprises a cationic modification. Preferably, the cationic modification comprises an amino group, such as a quaternary ammonium group.
[0039] Preferably, the polysaccharide backbone is cellulosic. Most preferably, the cellulosic backbone is hydroxyethyl cellulose.
[0040] A preferred polymer is polyquaternium-10 (PQ10), such as UCare from Dow. TM Polymer JR-30M is commercially available.
[0041] Ethoxylated anionic surfactants
[0042] The composition of the present invention comprises an ethoxylated anionic surfactant. The soluble ethoxylated anionic surfactant comprises ethylene oxide (EO) groups and has a degree of ethoxylation (n) of 3 to 15, preferably 5 to 15.
[0043] The ethoxylated anionic surfactant is preferably present in an amount of from 0.1 to 5 wt%, preferably from 0.1 to 2 wt%, based on the weight of the total composition.
[0044] Preferably, the ethoxylated anionic surfactant is linear.
[0045] The anion is preferably a phosphate or sulfate group.
[0046] Examples of preferred ethoxylated anionic surfactants are Oleth-10-Phosphate and PPG-5-Ceteth-10 Phosphate.
[0047] These products are available from Croda as Crodafos TM O10A and Crodafos TM SG obtained.
[0048] The level of ethoxylation can be measured by any suitable method. One method is by equilibrium headspace analysis.
[0049] Piroctone compounds
[0050] The piroctone compounds useful in the present invention generally have a structure defined by formula (A):
[0051]
[0052] Wherein R4 is selected from C1-C17 hydrocarbon group, R5 is selected from C1-4 alkyl, C2-4 alkenyl or alkynyl, hydrogen, phenyl or benzyl, and M1 is selected from hydrogen, monoethanolamine (MEA), diethanolamine (DEA) or triethanolamine (TEA). The preferred R4 group is (CH3)3CCH2CH(CH3)CH2-, and the preferred R5 is methyl. More preferably, R4 is (CH3)3CCH2CH(CH3)CH2-, R5 is methyl, and M1 is hydrogen or MEA. Most preferably, R4 is (CH3)3CCH2CH(CH3)CH2-, R5 is methyl, and M1 is monoethanolamine.
[0053] The piroctone compound used in the present invention is preferably selected from piroctone acid, primary ethanolamine salt of piroctone acid, secondary ethanolamine salt of piroctone acid and tertiary ethanolamine salt of piroctone acid, and mixtures thereof, more preferably selected from piroctone acid, primary ethanolamine salt of piroctone acid and mixtures thereof.
[0054] A preferred example of the primary ethanolamine salt of piroctone acid is piroctone olamine, which can be used as An example of a suitable secondary ethanolamine salt of pirocidonic acid is the diethanolamine salt; an example of a suitable tertiary salt of pirocidonic acid is the triethanolamine salt.
[0055] Particularly preferred is piroctone olamine.
[0056] Typical content of the piroctone compound is 0.001 to 2 wt%, preferably 0.01 to 1 wt%, more preferably 0.05 to 0.5 wt%, most preferably 0.05 to 0.3 wt%.
[0057] In the compositions and methods according to the present invention, some or all of the piroctone compounds are in dissolved form so that the composition is transparent. Some piroctone compounds may not be in dissolved form. The amount of undissolved AD agent is low enough to maintain the transparency of the composition.
[0058] Solvents
[0059] The solvent is preferably present to increase the solubility of the piroctone compound in the composition. The solvent enables more of the piroctone compound to be incorporated into the composition while maintaining transparency. The solvent is capable of dissolving the piroctone compound at ambient temperature. Typically, the ambient temperature is 20 to 30 degrees.
[0060] Preferred solvents are alcohols, preferably selected from propylene glycol (PG), dipropylene glycol (DPG) and mixtures thereof.
[0061] The solvent is preferably present in an amount of 0.025 to 5 wt%, more preferably 0.05 to 3 wt%, even more preferably 0.5 to 2 wt%, based on the total weight of the composition.
[0062] Cationic surfactants
[0063] The composition preferably comprises a cationic surfactant. The presence of a cationic surfactant aids clarity. This is particularly useful if other ingredients, such as fragrances, are added.
[0064] Preferred cationic surfactants may be selected from quaternary ammonium surfactants and tertiary ammonium surfactants.
[0065] Preferred cationic surfactants include coconut amine ethoxylates, for example, Ethomeen TM C / 25 or C / 15. And PEG-15 cocamine and PEG-2 cocamine and cetyltrimonium chloride (CTAC).
[0066] The compositions of the present invention comprise a cationic surfactant, preferably comprising an amino or quaternary ammonium hydrophilic moiety, which is positively charged when dissolved in an aqueous composition.
[0067] Examples of suitable cationic surfactants correspond to the following general formula:
[0068] [N(R1)(R2)(R3)(R4)]+(X)-
[0069] Wherein R1, R2, R3 and R4 are each independently selected from
[0070] (a) an aliphatic group of 1 to 22 carbon atoms, or
[0071] (b) hydrogen or polyoxyalkylene, hydroxyalkyl, aromatic, alkoxy, alkylamido, hydroxyalkyl, aryl, alkylaryl having up to 22 carbon atoms; and
[0072] X is a salt-forming anion such as those selected from the group consisting of halides (eg, chloride, bromide), acetate, citrate, lactate, glycolate, phosphate, nitrate, sulfate, and alkyl sulfate.
[0073] In addition to carbon and hydrogen atoms, aliphatic groups may contain ether linkages and other groups, such as amino groups. Longer chain aliphatic groups, for example, those of about 12 carbons or more, may be saturated or unsaturated.
[0074] Specific examples of such quaternary ammonium cationic surfactants of the above general formula are PEG-15 cocamine and PEG-2 cocamine, cetyltrimonium chloride (CTAC) and their salts wherein the chloride ion is replaced by other halides (e.g., bromide), acetate, citrate, lactate, glycolate, phosphate, nitrate, sulfate or alkyl sulfate.
[0075] In the preferred class of cationic surfactants of the above general formula, R1 is C2 to C 22 A saturated or unsaturated, preferably saturated, alkyl chain, and R 2 , R 3 and R 4 Each independently selected from CH3 and (CH2CH2O) n H, preferably (CH2CH2O) n H.
[0076] The content of cationic surfactant is preferably 0.05 to 5% by weight, preferably 0.1 to 2% by weight of the total composition. Some cationic surfactants can generate foam in the composition of the present invention. When present, the amount of cationic surfactant is such that the maximum foam height defined herein and so determined is not exceeded.
[0077] The additional acid used can be used to protonate the amine. Suitable acids include hydrochloric acid, citric acid, acetic acid, tartaric acid, fumaric acid, lactic acid, malic acid, succinic acid and mixtures thereof. Preferably, the acid is selected from acetic acid, tartaric acid, hydrochloric acid, lactic acid and mixtures thereof.
[0078] Mixtures of any of the above cationic surfactants may also be suitable.
[0079] Rheology modifier
[0080] Compositions of the invention preferably comprise a rheology modifier to improve the spreading of the composition on the hair. This typically thickens the composition.
[0081] If present, preferably the rheology modifier is present in an amount of 0.2 to 2 wt%, most preferably 0.5 to 1.5 wt%.
[0082] Preferably, the rheology modifier is a polysaccharide, preferably derived from cellulose.
[0083] Preferably, the rheology modifier is nonionic.
[0084] Preferably, the molecular weight of the structurant ranges from 500 kDa to 2 MDa.
[0085] Examples of suitable rheology modifiers include hydroxyethylcellulose (HEC), for example available under the trade name Natrosol in the SURFACE® series from Ashland. Another suitable example is Amaze XT available from Nouryon.
[0086] Preferred rheology modifiers include hydroxyethyl cellulose and hydroxypropyl methyl cellulose. The most preferred structurant is hydroxyethyl cellulose.
[0087] Transparency additives
[0088] The composition may contain a clarity aid to enhance clarity. The clarity aid is different from and is not intended to be the same as any of the solvents described above for the piroctone compound.
[0089] Clarity aids are particularly useful in solubilizing ingredients such as fragrances.
[0090] Preferred clarity aids are nonionic in nature. They can be selected from nonionic surfactants and nonionic emulsifiers.
[0091] A preferred clarity aid is polysorbate 20, for example, Tween TM , which is available from Croda, and Laureth-7, for example, Marlipal 24 / 70, which is available from Sasol.
[0092] Some clarity aids can generate foam in the compositions of the present invention. If present, the clarity aid is present in an amount that does not cause the foam height to exceed the maximum value defined herein. Thus, the clarity aid (if present) is preferably present in an amount of 0.1 to 5 wt %, more preferably 0.2 to 2 wt %, and most preferably 0.25 to 1.5 wt % of the total composition weight.
[0093] The composition of the present invention comprises water. The composition suitably comprises water in an amount of 60 to 98 wt%, preferably 80 to 97 wt%, most preferably 90 to 97 wt% based on the weight of the total composition.
[0094] The compositions of the present invention are preferably free of dispersed phases that interfere with clarity (ie, are insoluble), such as, for example, silicone emulsions.
[0095] This dispersed phase has dispersed droplets of water-insoluble materials, for example, conditioning agents. Examples of water-insoluble conditioning agents include non-silicone conditioning agents, which contain non-silicone oily or fatty materials, such as hydrocarbon oils, fatty esters, and mixtures thereof. Preferably, the water-insoluble conditioning agent is an emulsified silicone oil.
[0096] In the context of the present invention, free of dispersed phase means less than 0.1 wt%, preferably less than 0.05 wt%, more preferably less than 0.001 wt%, still preferably less than 0.0001 wt%, most preferably 0 wt% dispersed phase based on the weight of the total composition.
[0097] The pH of the composition is preferably from 3 to 7, more preferably from 3.5 to 6.5, most preferably from 5 to 6.
[0098] The composition is free of anionic, zwitterionic and amphoteric surfactants other than those defined in ii), such that the foam height of the composition does not exceed the maximum foam height.
[0099] In the context of the present invention, being free of anionic, zwitterionic and amphoteric surfactants other than those defined in ii) means that preferably the content of these foam-generating anionic, zwitterionic and amphoteric surfactants is less than 1.0 wt. %, more preferably less than 0.5 wt. %, more preferably less than 0.1 wt. %, still more preferably less than 0.001 wt. %, most preferably 0 wt. % surfactants, based on the total composition weight. For example, such surfactants may be present as "carryover" in the raw materials used for the composition of the present invention. The amount of surfactant is such that the foam height of the composition does not exceed the maximum foam height.
[0100] In particular, these anionic, zwitterionic and amphoteric surfactants preferably include the following types of surfactants:
[0101] Surfactants with an alkyl chain of less than 16 CC atoms;
[0102] Polyoxyethylene alkyl ether sulfates having an average molar number of ethylene oxide added ranging from 1 to 5, preferably 1 to 3;
[0103] Betaines (alkyl chain length less than 16). For example, oleyl betaine, caprylamidopropyl betaine, lauramidopropyl betaine, isostearylamidopropyl betaine and cocamidopropyl betaine;
[0104] amine oxides, such as laurylamine oxide and cocoamine oxide;
[0105] Cocoamide monoethanolamine (CMEA);
[0106] Amphoterate;
[0107] Taurates, isothionates, glycinates and sulfonates, for example, alpha-olefin sulfonates.
[0108] Further ingredients
[0109] Compositions according to the present invention may contain any of a number of ingredients commonly found in hair compositions.
[0110] Other ingredients may include deposition polymers, preservatives, colorants, polyols such as glycerol and polypropylene glycol, chelating agents such as EDTA, antioxidants such as vitamin E acetate, fragrances, antimicrobial agents, and pH adjusters such as acids, preferably organic acids. Each of these ingredients is present in an amount effective to achieve its purpose.
[0111] Preferably, further ingredients include flavourings, preservatives and antimicrobial agents.
[0112] Mixtures of any of the above active ingredients may also be used.
[0113] Typically, these ingredients may be included individually at a level of up to 5%, preferably 2%, most preferably up to 1% by weight of the total composition.
[0114] Embodiments of the present invention are given in the following examples, in which all percentages are provided by weight based on total weight unless otherwise indicated. Example
[0115] The invention will now be illustrated by the following non-limiting examples.In the examples and throughout the specification, all percentages are by weight based on the total composition unless otherwise stated.
[0116] Example 1 - Preparation of Compositions 1-4 According to the Invention and Comparative Compositions A & B
[0117] The following compositions were prepared, of which 1-4 are according to the invention and A and B are comparative compositions:
[0118] Conditioner Composition 1 comprises a cationic conditioning polymer, an ethoxylated anionic surfactant comprising 10 EO groups and 0.1 wt% piroctone olamine.
[0119] Conditioner Compositions 2-4 also contained a cationic surfactant, a rheology modifier, a solvent (propylene glycol or dipropylene glycol), and varying amounts of piroctone olamine.
[0120] Comparative conditioner composition A is representative of a typical prior art shampoo composition and comprises sodium lauryl ether phosphate (SLES) 1EO and cocamidopropyl betaine and 0.5 wt% piroctone olamine.
[0121] Comparative conditioner composition B was the same as composition 1, but without piroctone olamine.
[0122] The following commercially available shampoos were used in the following tests:
[0123] Control 1: In the piroctone olamine deposition test, a commercial anti-dandruff shampoo "Clear Antidandruff Nourishing Shampoo Anti Hair Fall Womens" was used as a control. This product contained 0.50% of Octopirox.
[0124] Control 2: In the piroctone olamine deposition and foam generation test, the commercial anti-dandruff shampoo "Head and Shoulders 2 in 1 Men Total Care with sea minerals" was used as a control. This product contains at least 0.50% of Octopirox.
[0125] The compositions of compositions 1-4 and A & B are given in Table 1 below:
[0126] Table 1: Compositions of compositions 1 to 4 according to the invention and comparative compositions A and B
[0127]
[0128]
[0129] The compositions in Table 1 were prepared as follows:
[0130] 1. Provide water (300 ml) at 25°C in a first container.
[0131] 2. When present, add hydroxyethylcellulose to the water with stirring for 2 minutes.
[0132] 3. Add cationic conditioning polymer (Polyquaternium-10) and stir the mixture for an additional 2 minutes.
[0133] 4. When present, add the cationic surfactant (PEG-15 cocoamine or PEG-2 cocoamine) and stir the mixture for an additional 2 minutes.
[0134] 5. In a second container, add the anionic surfactant along with any minor ingredients to water (35 ml) at 70°C and stir gently until dissolved.
[0135] 6. The resulting hot solution was then added to the mixture in the first container, which was heated to 40°C for 30 minutes with stirring at 100 rpm before cooling to room temperature.
[0136] 7. Add any remaining ingredients (flavor, polysorbate 20, citric acid, piroctone olamine (added as a slurry with water)) with continued stirring at 100 rpm.
[0137] Example 2 - Treatment of hair with conditioner compositions 1-4 according to the invention, comparative compositions A & B and shampoo controls 1 & 2 Deposition of piroctone olamine on treated hair
[0138] Hair treatment
[0139] Dark brown European virgin hair tresses (2.5 grams, 6 inches) were used in the following tests and procedures.
[0140] Before starting any treatment, pre-shampoo the tresses twice with a basic shampoo composition to remove any surface contamination. Wet each tress and then treat with 0.1 gram of shampoo per gram of hair and lather for 30 seconds, then rinse in running warm water for 30 seconds. Comb the hair and gently squeeze out excess water.
[0141] For the shampoo controls (Control 1 and 2) and Comparative Composition A, 0.1 g of shampoo per gram of hair was applied to the hair and lathered for 30 seconds, then rinsed in running warm water for 30 seconds. A second application and rinse were performed in the same manner. The hair was combed and excess water was gently squeezed out.
[0142] For each conditioner formulation (Compositions 1-4 and Composition B), 0.2 grams of the conditioner formulation per gram of hair was evenly applied to the washed hair tresses (3 tresses per composition) and massaged into the hair, then rinsed for 1 minute. Excess water was then gently removed and the tresses were dried in a drying oven at 50°C.
[0143] Note that the shampoo formulation is applied to the hair twice at 0.1 gram of product per gram of hair, with a rinsing phase after each application, whereas the conditioner formulation is applied to the hair once at 0.2 gram per gram of hair. These applications are typical of consumer behavior.
[0144] Extraction of Hair Tresses for Piroctone Olamine Deposition Analysis:
[0145] Each dried tress was placed in a suitable jar and about 10 ml of absolute ethanol was added. The jar was then sealed and placed on a roller bed for 1 hour, after which the extracted liquid was removed with a syringe.
[0146] Octopirox deposition on hair
[0147] The amount of Octopirox deposited on the hair was measured by HPLC. The results are given in Table 2 below.
[0148] Table 2 - Treatment with Conditioner Compositions 1 to 4 According to the Invention, Comparative Compositions A & B and Shampoo Controls 1 and 2 Deposition of Octopirox on Hair
[0149]
[0150]
[0151] Example 3 - Treatment of hair with conditioner compositions 1-4 according to the invention, comparative compositions A & B and shampoo controls 1 & 2 Deposition efficiency of Octopirox on treated hair
[0152] Deposition efficiency
[0153] Theoretical maximum deposition
[0154] The theoretical maximum deposition of Octopirox on the hair was calculated by taking the amount of Octopirox in the composition (wt%) and multiplying by the dose applied to the hair (0.2 grams) and expressed in ppm.
[0155] The measured Octopirox deposition (ppm) on the hair after treatment as described above can be divided by the theoretical maximum to give the deposition efficiency. This reflects the proportion of Octopirox that remains on the hair.
[0156] The deposition efficiencies are given in Table 3.
[0157] Table 3 - Theoretical maximum deposition, measured deposition and calculated deposition efficiency of piroctone olamine (Octopirox) on hair treated with conditioner compositions 1-4 according to the invention, comparative compositions A & B and shampoo controls 1 & 2
[0158]
[0159]
[0160] It can be seen that Octopirox deposition in these rinse-off products is an inefficient process, removing a large portion of the anti-dandruff benefit agent present during the rinsing step.
[0161] Control Shampoos 1 and 2 and Comparative Example A all delivered Octopirox with deposition efficiencies ranging from 0.80 to 1.16%.
[0162] Compositions 1-4 according to the invention delivered Octopirox with significantly higher deposition efficiencies ranging from 1.40 to 2.68%.
[0163] Example 4: Foaming properties of compositions 1 & 2 according to the present invention and comparative composition A
[0164] Consumers do not accept hair conditioners that foam during use. Foam is closely associated with cleansing rather than conditioning.
[0165] Conditioner compositions 1, 2 and A were evaluated for their foaming levels.
[0166] Cylinder vibration foam test
[0167] The level of foaming produced by the compositions of the present invention was measured at ambient temperature (25°C) and atmospheric pressure using the following method.
[0168] 1 gram of the test product is diluted with 9 grams of water and added to a 100 ml glass measuring cylinder, manufactured by Duran, supplied by VWR, and having an inner diameter of 29 mm. The starting volume (V1) is recorded. The cylinder is stoppered and then shaken vigorously vertically for 10 seconds. After a further 60 seconds of standing, the height of the foam is visually measured to the most acceptable 5 ml mark. From this value, the starting volume of the solution (V1 = 10 ml) is subtracted to calculate the amount of air entrained in the foam.
[0169] The results are shown in Table 4.
[0170] Table 4: Foam height of compositions 1, 2 and A
[0171]
[0172]
[0173] It can be seen that the composition of the present invention exhibits very low foam levels.
[0174] Example 5: Transparency of Compositions 1 to 4 According to the Invention and Comparative Composition B
[0175] The clarity of Conditioner Compositions 1-4 and B was evaluated by measuring turbidity. When the turbidity was less than 1.0 cm -1 The conditioner formulation is considered to be clear when
[0176] The clarity of each formulation was measured using a Jasco V-650 spectrophotometer. The absorbance at 750 nm was converted to turbidity values according to the following formula:
[0177] Turbidity = (2.3 x absorbance) / path length, where A is the absorbance measured from the sample at 750 nanometers and a path length of 1.0 centimeter.
[0178] The turbidity of compositions 1-4 and B is given in Table 5 below.
[0179] Table 5: Turbidity of Compositions 1-4 and B
[0180] Example <![CDATA[Turbidity (cm -1 )]]> Amount of Octopirox (wt%) 1 0.00 0.1 2 0.29 0.1+Transparency additive 3 0.01 0.15+transparency additive+PG 4 0.04 0.25+transparency additive+DPG B 0.01 0
[0181] The turbidity of transparent samples is less than 1.0 cm -1 .
[0182] • At the lowest level (0.1 wt%) of Octopirox (Example 1), clarity was achieved without clarity aids or solvents.
[0183] Example 2 shows that clarity can be maintained by adding clarity aids, even when rheology modifiers and cationic surfactants are introduced.
[0184] • Examples 3 and 4 show that excellent clarity can be achieved at higher Octopirox levels with the addition of solvent according to the present invention.
[0185] Example 6: Conditioning Performance of Compositions 2, 3 and a Commercially Available Clear Conditioner (Level of Friction on Treated Hair)
[0186] The friction level of the hair can be used as an indicator of the level of lubricity imparted to the hair by the conditioning treatment.
[0187] The coefficient of friction is a dimensionless number defined as the ratio between the friction force and the normal force.
[0188] The hair (5 g tress) was first wetted with water and treated with 1 g of composition (2 and 3), which was then diluted with 7 ml of water.
[0189] The coefficient of friction (CoF) was then determined by tapping the hair strands with a real finger on a custom instrumented force plate that measures force and torque in three dimensions using six force sensors.
[0190] A commercially available transparent conditioner "L'Oreal Fibrology Transparent Conditioner" was also used as a comparison.
[0191] The results are given in Table 6.
[0192] Table 6: Coefficient of Friction of Hair Treated with Compositions 2 and 3 and a Commercial Clear Conditioner
[0193] Composition CoF after adding 7 ml of water 2 0.32 3 0.32 L'Oreal Fibrology Transparent Conditioner 0.41
[0194] Compositions 2 and 3 provided excellent lower friction.
Claims
1. An aqueous conditioning agent composition comprising: i) 0.1 to 2% by weight of a cationic conditioning polymer; ii) 0.1 to 5% by weight of an ethoxylated anionic surfactant comprising ethylene oxide groups and having a degree of ethoxylation of 3 to 15; and iii) 0.001 to 2% by weight of a piroctone compound; The transparency of the composition is such that the turbidity is less than 1 cm -1 , as measured using a UV / vis spectrophotometer and applying the formula turbidity = (2.3 x A / L), where A is the absorbance measured from the sample at 750 nanometers, and L is the path length; wherein the composition has a maximum foam height of 10 ml as measured at 25°C and atmospheric pressure by diluting 1 gram of the composition with 9 grams of water in a 100 ml graduated cylinder having an inner diameter of 29 mm and recording the starting volume (V1); then stoppering the graduated cylinder and shaking it vertically vigorously for 10 seconds, followed by standing for 60 seconds, after which the height of the foam is measured to the nearest 5 ml mark; and subtracting the starting volume (V1) from this value; and wherein the composition is free of anionic, zwitterionic and amphoteric surfactants other than those defined in ii) such that the foam height of the composition does not exceed the maximum foam height.
2. The composition of claim 1 comprising 0.025 to 5% by weight of a solvent that dissolves the piroctone compound at ambient temperature.
3. The composition of claim 2, wherein the solvent is selected from the group consisting of propylene glycol, dipropylene glycol, and mixtures thereof.
4. The composition of claim 1, wherein the piroctone compound is selected from the group consisting of piroctone acid, primary ethanolamine salts of piroctone acid, secondary ethanolamine salts of piroctone acid, and tertiary ethanolamine salts of piroctone acid, and mixtures thereof.
5. The composition of claim 4, wherein the piroctone compound is piroctone olamine.
6. A composition as claimed in any preceding claim further comprising 0.05 to 5 wt%, preferably 0.1 to 2 wt% of a cationic surfactant.
7. The composition of claim 6, wherein the cationic surfactant is selected from quaternary ammonium surfactants and tertiary ammonium surfactants.
8. A composition as claimed in any one of the preceding claims, wherein the cationic conditioning polymer has a polysaccharide backbone, wherein the polysaccharide comprises a cationic modification.
9. The composition of claim 8, wherein the cationic modification comprises an amino group.
10. A composition as claimed in any preceding claim, wherein the degree of ethoxylation, n, of the ethoxylated anionic surfactant is from 5 to 15.
11. A composition as claimed in any preceding claim further comprising a rheology modifier, preferably a polysaccharide, in an amount of 0.2 to 2 wt%.
12. A composition as claimed in any preceding claim, further comprising a clarity aid, preferably selected from nonionic surfactants and nonionic emulsifiers.
13. A composition as claimed in claim 12, wherein the clarity aid is present in an amount of 0.1 to 5 wt%, more preferably 0.2 to 2 wt%, most preferably 0.25 to 1.5 wt%, so that the maximum foam height as defined in claim 1 is not exceeded.
14. A composition as claimed in any preceding claim which is free of a dispersed phase which affects the transparency.
15. A composition as claimed in any one of claims 1 to 14 for use in a non-therapeutic method comprising applying the composition to the hair or scalp.
Citation Information
Patent Citations
Contamination resistant cartridge valve
EP2944852A1
Hair treatment compositions and methods
WO2021144267A1